Regulation of the Two-Component Regulator CpxR on Aminoglycosides and β-lactams Resistance in Salmonella enterica serovar Typhimurium - Huang, Hui; Sun, Yawei; Yuan, Li; Pan, Yushan; Gao, Yanlin; Ma, Caihui; Hu, Gongzheng (Frontiers in Microbiology, 2016)
The two-component signal transduction system CpxAR is especially widespread in Gram-negative bacteria. It has been reported that CpxAR contributes to the multidrug resistance (MDR) in Escherichia coli. CpxR is a response regulator in the two-component CpxAR system. The aim of this study was to explore the role of cpxR in the MDR of S. enterica serovar Typhimurium. The minimal inhibitory concentrations (MICs) of various antibiotics commonly used in veterinary medicine for strains JS (a multidrug-susceptible standard strain of S. enterica serovar Typhimurium), JSΔcpxR, JSΔcpxR/pcpxR, JSΔcpxR/pcpxR*, JSΔcpxRΔacrB, JSΔcpxRΔacrB/pcpxR, JSΔcpxRΔacrB/pcpxR*, 9 S. enterica serovar Typhimurium isolates (SH1–9), and SH1–9ΔcpxR were determined by the 2-fold broth microdilution method. The relative mRNA expression levels of ompF, ompC, ompW, ompD, tolC, acrB, acrD, acrF, mdtA, marA, and soxS in strains JS, JSΔcpxR, and JSΔcpxR/pcpxR were detected by real-time PCR. The results showed 2- to 4-fold decreases in the MICs of amikacin (AMK), gentamycin (GEN), apramycin (APR), neomycin (NEO), ceftriaxone (CRO), ceftiofur (CEF), and cefquinome (CEQ) for strain JSΔcpxR, as compared to those for the parental strain JS. Likewise, SH1–9ΔcpxR were found to have 2- to 8-fold reduction in resistance to the above antibiotics, except for NEO, as compared to their parental strains SH1–9. Furthermore, 2- to 4-fold further decreases in the MICs of AMK, GEN, APR, and CEF for strain JSΔcpxRΔacrB were observed, as compared to those for strain JSΔacrB. In addition, CpxR overproduction in strain JSΔcpxR led to significant decreases in the mRNA expression levels of ompF, ompC, ompW, ompD, tolC, acrB, marA, and soxS, and significant increases in those of stm3031 and stm1530. Notably, after all strains were induced simultaneously by GEN to the 15th passage at subinhibitory concentrations, strain JSΔcpxR/pcpxR showed significant increases in mRNA expression levels of the efflux pump acrD and mdtA genes, as compared to strain JSΔcpxR. Our results indicate that the two-component regulator CpxR contributes to resistance of S. enterica serovar Typhimurium to aminoglycosides and β-lactams by influencing the expression level of the MDR-related genes.